2016
DOI: 10.5935/abc.20160015
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Functional Variables and Heart Failure after Myocardial Infarction in Rats

Abstract: BackgroundHeart failure prediction after acute myocardial infarction may have important clinical implications.ObjectiveTo analyze the functional echocardiographic variables associated with heart failure in an infarction model in rats.MethodsThe animals were divided into two groups: control and infarction. Subsequently, the infarcted animals were divided into groups: with and without heart failure. The predictive values were assessed by logistic regression. The cutoff values predictive of heart failure were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Cardiac remodeling can be defined as molecular, cellular, and interstitial modifications that are clinically manifested as changes in size, mass, geometry and heart function after cardiac injury. Heart dysfunction is the final sign of cardiac remodeling and is an important prognostic factor after MI, increasing the risk of death[ 45 , 46 ]. Diastolic dysfunction after MI refers to mechanical and functional abnormalities during relaxation and filling of the LV and is associated with hypertrophy and increased LA[ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac remodeling can be defined as molecular, cellular, and interstitial modifications that are clinically manifested as changes in size, mass, geometry and heart function after cardiac injury. Heart dysfunction is the final sign of cardiac remodeling and is an important prognostic factor after MI, increasing the risk of death[ 45 , 46 ]. Diastolic dysfunction after MI refers to mechanical and functional abnormalities during relaxation and filling of the LV and is associated with hypertrophy and increased LA[ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac function was reduced in MI-induced heart failure rats [ 27 ], mice [ 28 , 29 ], rabbits [ 30 ], and swines [ 31 ]. In the present study, the results showed that the EF and FS of LV in MI-induced heart failure rats were reduced, which were improved by miR-132 agomiR.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure was considered when three criteria were met: Pulmonary congestion: a) percentage of lung humidity above 80%; b) lung/body weight (BW) ratio greater than lung/BW approximately 2-fold in relation to C [21]; c) right lung/BW above 5 mg/g [22]. RV hypertrophy: characterized by the ratio of the weight of RV adjusted by BW above 0.8 mg/g [23]. Elevated LVEDP: LV end diastolic pressure (LVEDP) greater than 15 mmHg [24,25]; and Systolic dysfunction: maximum positive value of the first derivative of LV systolic pressure above 7000 mmHg [22].…”
Section: Heart Failurementioning
confidence: 99%